The classic slave narratives - Gates, Henry Louis, Jr. (New York, N.Y. : Signet Classics, 2002)
Before the end of the civil war, over one hundred former slaves had written moving stories of their captivity and by 1944, when George washington Carver published his autobiography, over six thousand ex-slaves ahd written what caalled slave narratives. No group of slaves anywhere, in any other ear, has left such prolific testimony to the horror of bondage and servitude.
The interesting narrative of the life of Olaudah Equiano, or, Gustavus Vassa, the African -- The history of Mary Prince, a West Indian slave -- Narrative of the life of Frederick Douglass, an American slave -- Incidents in the life of a slave girl / [Harriet Jacobs, writing as Linda Brent].
Includes bibliographical references (p. [669]-672).
Keywords: Slave narratives -- United States; Enslaved persons -- United States -- Biography; African Americans -- Biography; Enslaved persons' writings, American; Enslaved persons -- United States -- Social conditions; African Americans -- History -- To 1863.; United States -- Race relations; Equiano, Olaudah, -- 1745-1797.; Prince, Mary; Douglass, Frederick, -- 1818-1895.; Jacobs, Harriet A. -- 1813-1897.